Hepatitis B virus X protein recruits methyltransferases to affect cotranscriptional N6-methyladenosine modification of viral/host RNAs - Kim, Geon-Woo; Siddiqui, Aleem (Proceedings of the National Academy of Sciences - PNAS, 2021)
Chronic hepatitis B virus (HBV) infections are one of the leading causes of cirrhosis and hepatocellular carcinoma. N6-methyladenosine (m A) modification of cellular and viral RNAs is the most prevalent internal modification that occurs cotranscriptionally. Previously, we reported the dual functional role of m A modification of HBV transcripts in the viral life cycle. Here, we show that viral HBV X (HBx) protein is responsible for the m A modifications of viral transcripts. HBV genomes defective in HBx failed to induce m A modifications of HBV RNAs during infection/transfection, while ectopic expression of HBx restores m A modifications of the viral RNAs but not the mutant HBx carrying the nuclear export signal. Using chromatin immunoprecipitation assays, we provide evidence that HBx and m A methyltransferase complexes are localized on the HBV minichromosome to achieve cotranscriptional m A modification of viral RNAs. HBx interacts with METTL3 and 14 to carry out methylation activity and also modestly stimulates their nuclear import. This role of HBx in mediating m A modification also extends to host phosphatase and tensin homolog (PTEN) mRNA. This study provides insight into how a viral protein recruits RNA methylation machinery to m A-modify RNAs.